2008
DOI: 10.1136/ard.2006.057760
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiac abnormalities by Doppler echocardiography in a large nationwide multicentric cohort of patients with systemic sclerosis

Abstract: Left and right heart diseases, including PAH, LV hypertrophy and diastolic dysfunction, are common in SSc. However, a small subset of patients without any cardiac or pulmonary diseases have a restrictive mitral flow pattern that could be due to primary cardiac involvement of SSc. The prognostic implications of the LV abnormalities will be evaluated in the 3-year follow-up of this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 34 publications
3
85
2
2
Order By: Relevance
“…5 Additionally, SSc often causes left ventricular (LV) hypertrophy, nonsystolic LV dysfunction, and left atrial enlargement. 37 Overall, the cumulative infl uence of SSc on the heart may impair the heart's ability to compensate against increasing PVR in SSc-PAH. Our group has shown that despite similar hemodynamic indices, patients with SSc-PAH have higher mortality and are less responsive to therapy than patients with IPAH.…”
Section: Cardiac Involvement In Ssc-pahmentioning
confidence: 99%
“…5 Additionally, SSc often causes left ventricular (LV) hypertrophy, nonsystolic LV dysfunction, and left atrial enlargement. 37 Overall, the cumulative infl uence of SSc on the heart may impair the heart's ability to compensate against increasing PVR in SSc-PAH. Our group has shown that despite similar hemodynamic indices, patients with SSc-PAH have higher mortality and are less responsive to therapy than patients with IPAH.…”
Section: Cardiac Involvement In Ssc-pahmentioning
confidence: 99%
“…The presence of diastolic dysfunction in patients with SSc, detected by the majority of previous studies [19][20][21], was commonly demonstrated by pulsed wave Dopplerderived transmitral inflow patterns. However, the use of TDI, less influenced by loading conditions, suggests that the Em determined by pulsed TDI is more reliable than conventional transmitral Doppler flow [22].…”
Section: Discussionmentioning
confidence: 93%
“…The earliest, most frequent and characteristic echocardiographic feature of SHD is the left ventricular diastolic dysfunction, and multiple symptoms of SSc patients (including decreased exercise capacity, dyspnoea, and decompensation) are strongly related to LV filling pressure. Its prevalence ranges from 17.7% in a large cohort using traditional Doppler echocardiography11 to 63% in the latest studies performing tissue Doppler echocardiography 2. Left ventricular diastolic dysfunction is related to the degree of myocardial fibrosis and is inversely and independently associated to the survival of the patients 12…”
Section: Discussionmentioning
confidence: 99%